The Role of A'bulosibatang Local Culture and its Relationship with Taxpayer Compliance in Gowa Regency - Muhaimin, Muhaimin; Mira, Mira; Akila , Nur (SENTRALISASI, 2024)
This research was conducted aims to determine the effect of a'bulosibatang on taxpayer compliance. Qualitative research type, which is a way used to answer research problems related to data in the form of narratives This research is a descriptive qualitative research using interviews as a research instrument. The informants are the people of Gowa who have become active taxpayers and are registered at the KP2KP Gowa Testing is done by triangulation (data coding, data reduction and conclusion drawing). The results showed that efforts to efforts to increase public trust in accountability and transparency government must continue to be encouraged. WPOP compliance in gowa Regency especially in limbung shows compliance in paying taxes, where cultural values such as cultural values such as Mutual Assistance, cooperation play a key role in the implementation of tax obligations. implementation of tax obligations. As for the implications of this research, it is in terms of formulating policies and regulations relating to existing taxation and increasing public confidence in the government's financial regulations especially for the tax funds collected.  so that tax awareness and tax compliance becomes a joint responsibility as long as the government also contributes in terms of accountable and prosperous policies and management.